To simplify this expression, we first need to apply the exponent rule that states (a^m)^n = a^(m*n).
First, we simplify the expression within the parentheses:
4^7 = 16384
Now we rewrite the expression as:
4^2 * 16384^-4
Next, we simplify 16384^-4:
16384^-4 = 1 / 16384^4 = 1 / 1048576000000000
Now we rewrite the expression as:
4^2 * (1 / 1048576000000000)
Now we multiply 4^2 by the reciprocal of 1048576000000000:
4^2 * (1 / 1048576000000000) = 16 / 1048576000000000
Therefore, the simplified expression is:
16 / 1048576000000000
4^2*(4^7)^-4
1 answer